Mulberrofuran G inhibits proliferation and migration by inactivating JAK2/STAT3 signaling in lung cancer cells (Bangladesh Journal of Pharmacology, 2021)
The present study has investigated how mulberrofuran G affects prolifera-tion, invasion, and migration of the lung adenocarcinoma and squamous cell carcinoma. Four different concentrations of mulberrofuran G (1, 5, 10, and 100 μmol/L) were used to simulate human lung adenocarcinoma cells (A549 cells) and squamous-cell carcinoma (NCI-H226 cells). The results showed that mulberrofuran G significantly inhibited the proliferation, invasion, and migration of both A549 and NCI-H226 cells, with a dose-effect relationship. The IC50 inhibited the growth of A549 cells and NCI-H226 cells by mulberrofuran G were 22.5 and 30.6 μmol/L, respectively. It strengthened the expression of CDK4 and MMP9 but significantly weakened the expression of p27 in both A549 cells and NCI-H226 cells. Furthermore, the expression of p-JAK2 and p-STAT3 was significantly down-regulated in drug treatments. In conclusion, mulberrofuran G could inhibit proliferation, migration, and invasion of lung cancer cells via inactivating JAK2/STAT3 signaling.